Founding faith: providence, politics, and the birth of religious freedom in America - Waldman, Steven (Random House, 2008)
The culture wars have distorted the dramatic story of how Americans came to worship freely. Author Waldman, cofounder of Beliefnet.com, argues that the United States was not founded as a "Christian nation," nor were the Founding Fathers uniformly secular or Deist. Rather, the Founders forged a new approach to religious liberty, a revolutionary formula that promoted faith--by leaving it alone. His narrative begins with early settlers' stunningly unsuccessful efforts to create a Christian paradise, and concludes with the presidencies of Washington, Adams, Jefferson, and Madison, during which the men who had devised lofty principles regarding the proper relationship between church and state struggled to practice what they'd preached.--From publisher description